2018
DOI: 10.1002/we.2290
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine gearbox failure and remaining useful life prediction using machine learning techniques

Abstract: This research investigates the prediction of failure and remaining useful life (RUL) of gearboxes for modern multi‐megawatt wind turbines. Failure and RUL are predicted through the use of machine learning techniques and large amounts of labelled wind turbine supervisory control and data acquisition (SCADA) and vibration data. The novelty of this work stems from unprecedented access to one of the world's largest wind turbine operational and reliability databases, containing thousands of turbine gearbox failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 24 publications
0
45
0
1
Order By: Relevance
“…Oil particle counting [6] and operation data analysis (especially temperatures, as, for example, in [7][8][9][10][11]) are widely used techniques for condition monitoring: they are more easily interpretable, but the drawback is that they furnish a later stage and more uncertain fault diagnosis, with respect to sub-component vibration spectra analysis. This remark is supported quantitatively in the work [12], where large amounts of labeled wind turbine supervisory control and data acquisition (SCADA) and vibration data have been processed, and the conclusion is that operation data can be used for reliably diagnosing a failure approximately one month before it occurs, while high frequency vibration data can be used to extend the accurate prediction capability to five to six months before failure. Furthermore, using operation data analysis, the fault diagnosis can successfully be performed through Artificial Intelligence techniques approximately 75% of the time, while, using vibration data, this percentage rises to 100%.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Oil particle counting [6] and operation data analysis (especially temperatures, as, for example, in [7][8][9][10][11]) are widely used techniques for condition monitoring: they are more easily interpretable, but the drawback is that they furnish a later stage and more uncertain fault diagnosis, with respect to sub-component vibration spectra analysis. This remark is supported quantitatively in the work [12], where large amounts of labeled wind turbine supervisory control and data acquisition (SCADA) and vibration data have been processed, and the conclusion is that operation data can be used for reliably diagnosing a failure approximately one month before it occurs, while high frequency vibration data can be used to extend the accurate prediction capability to five to six months before failure. Furthermore, using operation data analysis, the fault diagnosis can successfully be performed through Artificial Intelligence techniques approximately 75% of the time, while, using vibration data, this percentage rises to 100%.…”
Section: Introductionmentioning
confidence: 87%
“…In [19], a critical analysis of the synchrosqueezing transform for the representation of non-stationary signals is proposed: for this aim, the synchrosqueezing transform is improved using iterative generalized demodulation and the proposed method is validated using both numerically simulated and experimental vibration signals of wind turbines planetary gearboxes. Finally, for comprehensive and recent reviews about wind turbine drive-train condition monitoring techniques, refer to [12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Defect identification challenges resulting from the lower speed of the MB may be partially mitigated by recording longer sampling periods of vibration data. For example, a ten second data acquisition period has been found to be less successful in detecting low speed bearing defects than for high speed bearing/gear tooth defects (Carroll et al, 2019). This suggests that one cause of reduced detection rates for faults in low speed bearings may therefore be due to insufficient sampling periods.…”
Section: Fault Diagnosis and Prognosismentioning
confidence: 99%
“…Yang et al [15] proposed a prediction model based on the double-layer convolutional neural network (CNN) to predict the remaining useful life of the bearing. Carrol et al [16] used ANN, support vector machine (SVM), and logistic regression to predict the remaining life of a gearbox and found that the ANN method has the highest prediction accuracy. Li et al [17] established a RUL prediction model for lithium batteries based on Elman neural network and verified the feasibility of the model in prediction.…”
Section: Introductionmentioning
confidence: 99%